The Role of the Higher Education Accreditation Commission in the Development of University Education in Jordan from the Perspective of Faculty Members in Jordanian Universities - Amad Ababnh (University of Science and Technology, Yemen, 2014)
The study aimed to identify the point view of faculty members in the role of the Higher Education Accreditation Commission in the development of education in Jordan's universities .The Egyptian instrument " survey of faculty members on issues of higher education in Egypt" was adapted. The content validity for the instrument was examined through a group of experts, and the internal consistency reliability which has been calculated by using Cronbach's  alpha method was 0.82. The instrument  administered on 921 faculty members. The main study findings were :the most faculty members believe that the role of the commission is positive, the percentages in the private universities was higher than in the public universities, in addition to that about one-third of faculty members do not know if the commission role is positive or negative. Furthermore, the results showed that the majority of faculty members somehow convinced to very convinced on the necessity of the application of accreditation standards in their colleges, in addition to that the results showed that there is a positive correlation between the degree of faculty members conviction ,the type of the university, and the satisfaction degree of the faculty members for the crowdedness in the college and the academic environment in the university .The study recommended to design and implement an awareness programs , fostering the application of accreditation standards in public universities. Key Words: Higher Education Accreditation Commission , University Education , Faculty Members , Jordanian Universities.